Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fimmu.2019.02812
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Receptors and Pro-inflammatory Cytokines Are Modulated in Common Variable Immunodeficiency Patients: Correlation With Ig Replacement Therapy

Abstract: Adiponectin exerts beneficial pleiotropic effects through three receptors, AdipoR1, AdipoR2, and T-cadherin; it also exerts immunomodulatory effects. We previously demonstrated that adiponectin levels are altered in common variable immunodeficiency disease (CVID). The purpose of the present study was to investigate further the specific involvement of adiponectin in CVID by characterizing (i) the expression profile of adiponectin receptors on peripheral blood mononuclear cells; (ii) the levels of another releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…A study reported the decreased expression of total AdipoQ and its high molecular weight oligomers in patients with common variable immunodeficiency ( Pecoraro et al, 2017 ). A further study also revealed different expression patterns of AdipoQR1 and AdipoQR2 in the peripheral blood mononuclear cells of these patients ( Polito et al, 2019 ).…”
Section: Adipoq and Brain Targetsmentioning
confidence: 88%
“…A study reported the decreased expression of total AdipoQ and its high molecular weight oligomers in patients with common variable immunodeficiency ( Pecoraro et al, 2017 ). A further study also revealed different expression patterns of AdipoQR1 and AdipoQR2 in the peripheral blood mononuclear cells of these patients ( Polito et al, 2019 ).…”
Section: Adipoq and Brain Targetsmentioning
confidence: 88%
“…For example, IL10 is often found to be upregulated in CVID as compared to healthy controls [17,18], but in a different cohort, a decrease of serum IL10 was described [19]. Overall, markers associated with an activated myeloid compartment are consistently upregulated in CVID [18][19][20], and the T-helper (Th) serum cytokine profile observed in immune dysregulation in CVID is mostly found to be Th-1 driven [17,18,21]. Varying findings in these studies highlight the need to consider CVID patients with immune dysregulation (CVIDid) separately from patients with an "infection only" (CVIDio)phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…IgG, IgM and IgA levels have been measured before and after the first Ig replacement therapy: the increase of levels of IgG is statistically significant as previously reported in patients with common variable immunodeficiencies and patients with X-linked agammaglobulinemia 13 (Table 1). To verify the specific changes that taken place after the first IgG infusion therapy, we measured Adiponectin after 24 h as we previously reported that modification in the adiponectin levels are already evident at 24 h postinfusion and therefore we considered adiponectin as a marker of functional changes post-infusion 5,6 . We confirmed that adiponectin but not leptin was statistically different at T0 and T1 post-IgG infusion (4.3 ± 4.53 vs 12.84 ± 8.78, respectively, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have been devoted to characterize the cytokines profile in CVID, albeit with conflicting results [4][5][6] . We recently reported that adiponectin is decreased in CVID and correlated to the first Ig infusion, representing a serum biomarker of functional changes taking place in the adipose and related to the replacement therapy 7 .…”
mentioning
confidence: 99%